Enhancement of Simvastatin dissolution by surface solid dispersion: effect of carriers and wetting agents - Ebtessam Ahmed Essa, Mai Dwaikat (Journal of Applied Pharmaceutical Science, 2015)
The aim of this work was to improve the aqueous solubility of simvastatin using the surface solid dispersion (SSD) technique. Water soluble (mannitol and lactose) and insoluble (Avecil PH101) carriers were used. The effect of the addition of polymeric wetting agents (namely PEG6000, Pluronic F68, Myrj 52 and PVP K-30) to drug/carrier composite was also investigated. SSD was prepared by solvent evaporation technique. All formulations were studied regarding the dissolution behavior and solid state characterization (DSC, FT-IR and X-ray diffraction). Both water soluble and insoluble carriers improved dissolution behaviour compared to unprocessed drug, with the former showing the best results. Addition of wetting agent to the water insoluble carrier greatly improved drug dissolution, with PVP K-30 showing better dissolution parameters that was comparable to that of marketed product. Physical state characterization using DSC indicated the marked reduction in drug crystallinity. Xray diffraction confirmed drug amorphousness. The results indicated that SSD may serve as a successful strategy for enhancing solubility of poorly water soluble drugs by proper manipulation of the used additives.
Keywords: Simvastatin, poor water solubility, surface solid dispersion. enhancing dissolution, solid dispersion.